Tuning laser-induced band gaps in graphene - Calvo, Hernan Laureano (2011)
Could a laser field lead to the much sought-after tunable band gaps in graphene? By using Floquet theory combined with Green’s functions techniques, we predict that a laser field in the mid-infrared range can produce observable band gaps in the electronic structure of graphene. Furthermore, we show how they can be tuned by using the laser polarization. Our results could serve as a guidance to design optoelectronic nanodevices.